Visual Outcomes of the FemtoLASIK Technology Using Excimer Lasers with Frequency More 1000 Hz in Low to Moderate Myopia Correction - A. V. Doga; I. A. Mushkova; A. N. Karimova; E. V. Kechin; A. E. Kopylov (Oftalʹmologiâ, 2021)
Purpose: to evaluate the clinical and functional results of the operation the FemtoLASIK by excimer lasers with frequency more 1000 Hz in patients with low to moderate myopia.Patients and methods. The 84 eyes of 84 patients with low to moderate myopia who had undergone FemtoLASIK procedure using with excimer lasers: Schwind Amaris 1050 Hz (Germany) and Microscan Visum 1100 Hz (Russia) were included in the study. The “Schwind Amaris 1050 Hz” and “Microscan Visum 1100 Hz” groups were comparable in terms of pre-operative data (age, sex, corneal curvature, central thickness of the cornea, sphere, cylinder, SE) (p > 0.05). All patients underwent complete ophthalmological examination before refractive laser surgery, and also patients were examined on the 1st day and 1 month after FemtoLASIK.Results. One month postoperatively, in the “Schwind Amaris 1050 Hz” group the UDVA 1.0 or better (20/20 or better by Snellen) was achieved in 100 %, in the “Microscan Visum 1100 Hz” group — in 100 % (p > 0.05). There wasn’t observed a loss of the CDVA lines in both groups. In the “Schwind Amaris 1050 Hz” group gain of one or more lines of the CDVA was 14 %, in the “Microscan Visum 1100 Hz” group — in 12.2 % (p > 0.05). In the “Schwind Amaris 1050 Hz” group the predictability of targeted refraction within ±0.5 D was in 90.7, within ± 1.0 D — in 100 %, in the “Microscan Visum 1100 Hz” group — in 90.2 % and 100 %, respectively (p > 0.05).Conclusions. The FemtoLASIK procedure using with different high-frequency excimer lasers is an effective, safe and predictable method for correcting low to moderate myopia.